First pass effect as an independent predictor of functional outcomes in medium vessel occlusions: an analysis of an international multicenter study - Radu, Răzvan Alexandru; Costalat, Vincent; Fahed, Robert; Ghozy, Sherief; Siegler, James E; Shaikh, Hamza; Khalife, Jane; Abdalkader, Mohamad; Klein, Piers; Nguyen, Thanh N; Heit, Jeremy J; Sweid, Ahmad; et al. (European stroke journal, 2024)
Introduction: First pass effect (FPE), achievement of complete recanalization (mTICI 2c/3) with a single pass, is a significant predictor of favorable outcomes for endovascular treatment (EVT) in large vessel occlusion stroke (LVO). However, data concerning the impact on functional outcomes and predictors of FPE in medium vessel occlusions (MeVO) are scarce. - Patients and Methods: We conducted an international retrospective study on MeVO cases. Multivariable logistic modeling was used to establish independent predictors of FPE. Clinical and safety outcomes were compared between the two study groups (FPE vs non-FPE) using logistic regression models. Good outcome was defined as modified Rankin Scale 0-2 at 3 months. - Results: Eight hundred thirty-six patients with a final mTICI ⩾ 2b were included in this analysis. FPE was observed in 302 patients (36.1%). In multivariable analysis, hypertension (aOR 1.55, 95% CI 1.10-2.20) and lower baseline NIHSS score (aOR 0.95, 95% CI 0.93-0.97) were independently associated with an FPE. Good outcomes were more common in the FPE versus non-FPE group (72.8% vs 52.8%), and FPE was independently associated with favorable outcome (aOR 2.20, 95% CI 1.59-3.05). 90-day mortality and intracranial hemorrhage (ICH) were significantly lower in the FPE group, 0.43 (95% CI, 0.25-0.72) and 0.55 (95% CI, 0.39-0.77), respectively. - Conclusion: Over 2/3 of patients with MeVOs and FPE in our cohort had a favorable outcome at 90 days. FPE is independently associated with favorable outcomes, it may reduce the risk of any intracranial hemorrhage, and 3-month mortality.